Impact of Psychological Empowerment on Organizational Citizenship Behavior among Nurses in Public Health Establishments of Proximity - Hamadouche, Abdessalam; Nekbil, Abdelmalih; Benkherouf, Amina; Lebouazda, Abdelhak; Maouche, Abdelhamid (Journal of Neonatal Surgery, 2026)
This study aims to examine the impact of psychological empowerment on organizational citizenship behavior (OCB) and to investigate potential gender differences in psychological empowerment among nurses working in Public Health Establishments of Proximity (PHEP). A quantitative descriptive–analytical design was adopted. The study sample consisted of 123 nurses. Data were collected using the Psychological Empowerment Scale and the Organizational Citizenship Behavior Checklist (OCB-C). The results indicated a statistically significant positive relationship between psychological empowerment and organizational citizenship behavior. In contrast, no statistically significant gender differences in psychological empowerment were observed among the participants. These findings highlight the importance of enhancing psychological empowerment as a means of promoting organizational citizenship behaviors in healthcare settings.